DEVELOPING STUDENTS’ READING ACHIEVEMENT USING PORPE TECHNIQUE - Nurhadiyanti (Language and Education Journal, 2021)
The purpose of this study was to examine the application of the PORPE technique in enhancing the eleventh-grade students’ reading achievement of SMAN 3 Unggulan Kayuagung. Since there were five classes with 157 students, the samples were selected using purposive sampling. As a result, there were 62 students who took part as the sample. This study used a quasi-experimental design with nonrandomized pretest and posttest control groups. The data was gathered employing a written test, which was a multiple-choice reading test. The data was analyzed using the ttest. The results revealed that students who were taught through PORPE technique scored higher on reading tests. Besides, PORPE technique could improve the eleventh grade students’ reading achievement of SMAN 3 Unggulan Kayuagung. Hence, students could understand the information form the text and were confidence in answering the questions